2022
DOI: 10.3390/jcm11041033
|View full text |Cite
|
Sign up to set email alerts
|

Direct Transport to Cardiac Arrest Center and Survival Outcomes after Out-of-Hospital Cardiac Arrest by Urbanization Level

Abstract: Current guidelines for post-resuscitation care recommend regionalized care at a cardiac arrest center (CAC). Our objectives were to evaluate the effect of direct transport to a CAC on survival outcomes of out-of-hospital cardiac arrests (OHCAs), and to assess interaction effects between CAC and urbanization levels. Adult EMS-treated OHCAs with presumed cardiac etiology between 2015 and 2019 were enrolled. The main exposure was the hospital where OHCA patients were transported by EMS (CAC or non-CAC). The outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…These hospitals will be called cardiac arrest centres (CAC) in the following years both in the US [ 71 ] and in Europe [ 72 , 73 ]. A recent study from Korea [ 74 ] on a vast sample of patients (more than 95,000) showed that the direct transport to a CAC was associated with an increased survival of about two times. Interestingly, at least for patients with a shockable presenting rhythm, the benefit in survival was independent of the time needed to reach the CAC, meaning that a longer transport but to a CAC was preferable to a shorter transfer but to a non-CAC [non-CAC 8 min; non-CAC 8 min: OR 0.40 (95% CI 0.12–1.32); CAC 8 min: OR 1.92 (95% CI 1.26–2.94); CAC 8 min: OR 1.78 (95% CI 1.03–3.10)] [ 75 ].…”
Section: The Role Of a Multidisciplinary Approach: The Cardiac Arrest...mentioning
confidence: 99%
“…These hospitals will be called cardiac arrest centres (CAC) in the following years both in the US [ 71 ] and in Europe [ 72 , 73 ]. A recent study from Korea [ 74 ] on a vast sample of patients (more than 95,000) showed that the direct transport to a CAC was associated with an increased survival of about two times. Interestingly, at least for patients with a shockable presenting rhythm, the benefit in survival was independent of the time needed to reach the CAC, meaning that a longer transport but to a CAC was preferable to a shorter transfer but to a non-CAC [non-CAC 8 min; non-CAC 8 min: OR 0.40 (95% CI 0.12–1.32); CAC 8 min: OR 1.92 (95% CI 1.26–2.94); CAC 8 min: OR 1.78 (95% CI 1.03–3.10)] [ 75 ].…”
Section: The Role Of a Multidisciplinary Approach: The Cardiac Arrest...mentioning
confidence: 99%